Nitrogen Removal From Nitrate-Containing Wastewaters in Hydrogen-Based Membrane Biofilm Reactors via Hydrogen Autotrophic Denitrification: Biofilm Structure, Microbial Community and Optimization Strategies - Dong, Kun; Feng, Xinghui; Yao, Yi; Zhu, Zongqiang; Lin, Hua; Zhang, Xuehong; Wang, Dunqiu; Li, Haixiang (Frontiers in Microbiology, 2022)
The hydrogen-based membrane biofilm reactor (MBfR) has been widely applied in nitrate removal from wastewater, while the erratic fluctuation of treatment efficiency is in consequence of unstable operation parameters. In this study, hydrogen pressure, pH, and biofilm thickness were optimized as the key controlling parameters to operate MBfR. The results of 653.31 μm in biofilm thickness, 0.05 MPa in hydrogen pressure and pH in 7.78 suggesting high-efficiency NO3−−N removal and the NO3−−N removal flux was 1.15 g·m−2 d−1. 16S rRNA gene analysis revealed that Pseudomonas, Methyloversatilis, Thauera, Nitrospira, and Hydrogenophaga were the five most abundant bacterial genera in MBfRs after optimization. Moreover, significant increases of Pseudomonas relative abundances from 0.36 to 9.77% suggested that optimization could effectively remove nitrogen from MBfRs. Membrane pores and surfaces exhibited varying degrees of calcification during stable operation, as evinced by Ca2+ precipitation adhering to MBfR membrane surfaces based on scanning electron microscopy (SEM), atomic force microscopy (AFM) analyses. Scanning electron microscopy–energy dispersive spectrometer (SEM–EDS) analyses also confirmed that the primary elemental composition of polyvinyl chloride (PVC) membrane surfaces after response surface methodology (RSM) optimization comprised Ca, O, C, P, and Fe. Further, X-ray diffraction (XRD) analyses indicated the formation of Ca5F(PO4)3 geometry during the stable operation phase.